Gastrointestinal bleeding in children: diagnosis, analysis, and structure - V.A. Dihtiar; M.V. Savenko; O.M. Barsuk; S.O. Shchudro; M.O. Kaminska (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2023)
The incidence of gastrointestinal bleeding is a significant concern among adult patients with gastrointestinal tract (GIT) disorders, as it is a leading cause of mortality. However, there is growing evidence of changes in the pattern of gastrointestinal pathologies among children, primarily attributed to an increasing number of cases related to peptic ulcer disease (PUD) and erosive processes of the GIT. Purpose - to investigate the prevalence and analyze changes in the structure of GIT diseases in children complicated by upper gastrointestinal bleeding (GIB), based on esophagogastroduodenoscopy (EGD) data. Materials and methods. Based on the clinic's records, a total of 4,457 children underwent EGD at the Regional Medical Center of Family Health in Dnipro. Among them, 1,393 (31.25%) patients were admitted to the surgical department with suspected GIB. In 201 (14.4%) cases, EGD was performed during active bleeding to determine its origin. The utilization of EGD during the acute phase in patients with suspected GIB is considered highly effective for both diagnosing the bleeding source and initiating early-stage treatment. The data were processed using the methods of variation statistics using the Statistica v 6.1 software package. To compare the relative indicators, the Pearson Hi-quadrat test (χ2) and the two-sided Fisher's exact test (TCF) were used. The critical level of statistical significance (p) was accepted as <0.05. Results. To conduct a comparative analysis of diagnosed cases of GIB, two groups of children with endoscopically confirmed GIB were formed: the Group I (n=125) representing the period of 2012-2013, and the Group II (n=201) - the period of 2020-2021. The results revealed an increase of 1.6 times in the number of patients with upper GIT diseases accompanied by bleeding in the Group II. Additionally, a significant rise in the frequency of GIT diseases, specifically erosive esophagitis, was observed. The number of patients with erosive esophagitis tripled in the Group II compared to the Group I. Conclusions. In recent years, there has been a notable rise in GIT diseases accompanied by upper GIB. The number of such cases increased by 1.6 times, from 125 to 201 patients. Notably, there is a pronounced increase in the incidence of erosive esophagitis, particularly among children in the early and younger age groups. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of participating institution. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.